Particulate organic carbon dominates early-stage soil carbon accumulation in restored mangroves across estuarine zones - Leiyu Wang; Dalong Jiang; Zuo Xu; Tao Nie; Meiling Hong (Journal of Environmental Management, 2026)

Predicting ecological risks of heavy metals in watersheds based on interpretable machine learning models: under the framework of data scarcity - Hong Chen; Meiling Kong; Zhenghua Wu; Liu Gong; Lanlan Huang; Yihan Li; Fazhi Xie (Environmental Monitoring and Assessment, 2026)

Comparison of Meltpro Myco Assay with MALDI-TOF Mass Spectrometry for rapid and accurate detection of clinical Mycobacterium Species - Kehao Peng; Liuyue Xu; Xuezhi Wang; Jianming Hong; Gengchen Zhang; Yuchuan Zhao; Yinong Ye; Zengqi Huang; Jinmei Zhang; Yuchun Huang; Zhiqiao Wu; Xiaolin Yu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Impact of environmental salinity on the MAPK-NFAT5 pathway in Trachemys scripta elegans and its role in osmoregulaton - Xin Niu; Yingnan Lu; Yue Yuan; Jiao Li; Yunjuan Xiao; Haitao Shi; Meiling Hong; Li Ding (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Altering wilting time and chopping length to optimize Medicago polymorpha L. fermentation ripening rate and flavour - Ning Mao; Hanyu Zhang; Ermei Du; Meiling Fan; Shihao Liu; Chaosheng Liao; Chao Chen; Hong Sun; Yulong Zheng; Ping Li; Yixiao Xie (Food Bioscience, 2025)

Liver transcriptome analysis reveals the molecular response to hibernation challenge in the Chinese soft-shelled turtle (Pelodiscus sinensis) - Muhammad Shahid Iqbal; Xiaoqi Ai; Qingjun Zhu; Ijaz Khan; Zeeshan Ali; Tian Lan; Li Ding; Meiling Hong (Frontiers in Marine Science, 2025)
Hibernation is a physiological strategy animals use to survive in hostile environments with extreme temperature challenges and food scarcity. During this state, significant changes occur in metabolism and cellular function, with numerous stress response pathways recalibrated to survive physiological challenges that could otherwise be fatal. Numerous studies were performed to explain the molecular mechanisms of mammalian hibernation, but detailed analyses remain scarce in reptiles. Given the limited understanding of the mechanisms regulating hibernation, we performed a comprehensive analysis of liver gene expression in the Chinese softshell turtle ( Pelodiscus sinensis ) comparing summer active (SA), hibernation (H), and early arousal (EA) states using RNA-sequencing. A total of 435 million high-quality reads were generated, identifying 3,508, 3,607, and 2,993 differentially expressed genes (DEGs) in the SA vs. H, H vs. EA, and EA vs. SA respectively. Gene ontology analysis revealed a shift in metabolic fuel utilization, with the down-regulation of metabolic and cellular processes during hibernation, reflecting a conserved strategy for energy conservation. The transition from hibernation to early arousal was marked by up-regulation of immune-related genes (e.g., CXCL12, ITGA4, PIGR) and endocrine regulators (e.g., CDKN1A, DLL4, IGF1R), facilitating metabolic recovery and cellular protection. Besides, we observed dynamic changes in carbohydrate and lipid metabolism, with down-regulation of hexokinase 2 (HK2) and glucose transporters during hibernation, and up-regulation of lipid metabolism genes (LSS, GPLD1) to support membrane integrity and signaling. Our findings provide insights into the molecular mechanisms underlying hibernation and arousal in ectotherms, with implications for understanding metabolic adaptations, immune regulation, and stress responses in extreme conditions.

Facile solvothermal synthesis of ultrafine platinum nanowires on carbon nanotubes to enhance hydrogen evolution performance - Chang-An Zhou; Meiling Ran; Huixi Chen; Tingting Ma; Chunhui Wu; Hong Zhang; Lei Song; Chao Wang; Kui Ma; Hairong Yue (Fuel, 2025)

Highly selective capture of Ni2+ from complex environments by a sandwich-like layered metal sulfide ion exchanger - Mingdong Zhang; Qisheng Hong; Yuan Aocheng; Yan Zhang; Xiaoying Huang; Meiling Feng; Jingli Mu (Journal of Hazardous Materials, 2025)

Research on antibiotic resistance genes in wild and artificially bred green turtles (Chelonia mydas) - Xin Niu; Liu Lin; Ting Zhang; Xiaoyu An; Yupei Li; Yangfei Yu; Meiling Hong; Haitao Shi; Li Ding (Science of The Total Environment, 2024)

Visible-light-assisted peroxymonosulfate activation using MIL-88A(Fe)/BiOI heterojunction composite to drive charge transport for eliminating acid red 18 - Meiling Wang; Xiaochun Liu; Kebin Li; Wenting Huo; Hong Wei; Hongna Zhang; Nannan Zhong; Hai-Ying Jiang (Journal of Environmental Chemical Engineering, 2024)

Exposure to butylparaben induces oxidative stress and apoptosis in the liver of Polypedates megacephalus tadpole - Xiaoqi Ai; Muhammad Shahid Iqbal; Rui Lin; Xia Wu; Lijun Wang; Meiling Hong (Frontiers in Marine Science, 2024)
Butylparaben (BuP) is a ubiquitous preservative in cosmetics, foods, and medicine. As an emerging pollutant, it has gained wide attention in recent years. Because amphibians have both aquatic and terrestrial life stages and high skin permeability, they are sensitive to environmental changes. To assess the toxic effects of BuP on amphibians, the present study was conducted on the spot-legged tree frog ( Polypedates megacephalus ) tadpoles. In the present study, LC 50 of BuP for 96 h exposures was 3509 µg/L. Then, the tadpoles were exposed to 0, 350 and 2100 µg/L BuP (hereafter named as CK, B1 and B2) for 12, 24 and 48 h, the oxidative stress and apoptosis in the liver were analyzed. The results showed that the content of MDA and activity of SOD and GSH-PX were increased with an increase in BuP exposure. BuP stress significantly altered the expression of Nrf2-Keap1 signal pathway genes. An increase in the expression of JAK-STAT signal pathway genes was observed with an increase in the exposure to BuP concentration at 24 and 48 h. In contrast, the expression of negative regulators of JAK-STAT signal pathway were significantly increased at 12 h and decreased at 24 and 48 h. A significant decrease in pro-apoptosis genes expression ( Bax and Caspase3 ) were observed at 12 h but increased at 24 and 48 h, while the expression of anti-apoptosis gene ( Bcl-2 ) decreased at 24 and 48 h. These results provide a valuable reference point for assessing the ecological and health risks associated with BuP in the environment.

2,3-pyridinedicarboxylic acid-modified MIL-88A(Fe) for enhanced peroxymonosulfate activation to degrade organic contaminants - Meiling Wang; Xiaochun Liu; Kebin Li; Wenting Huo; Hong Wei; Hai-Ying Jiang (Journal of Water Process Engineering, 2024)

Seasonal changes in hepatic lipid metabolism and apoptosis in Chinese soft-shelled turtle (Pelodiscus sinensis) - Xiaoqi Ai; Rui Lin; Zeeshan Ali; Qingjun Zhu; Li Ding; Haitao Shi; Meiling Hong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Embryonic development and transcriptomic analysis in red-eared slider Trachemys scripta elegans under salinity stress - Jing Lin; Yuchen Kong; Haitao Shi; Meiling Hong; Li Ding (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Comparative toxic effect of ammonia exposure on Mauremys sinensis and invasive species Trachemys scripta elegans - Li Ding; Zubin Huang; Lingyue Liang; Haitao Shi; Zhenhua Fang; Meiling Hong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Effects of butyl paraben on behavior and molecular mechanism of Chinese striped-necked turtle (Mauremys sinensis) - Xia Wu; Ijaz Khan; Xiaoqi Ai; Jiliang Zhang; Haitao Shi; Ding Li; Meiling Hong (Aquatic Toxicology, 2024)

Rice husk hydrochar prepared by hydrochloric acid assisted hydrothermal carbonization for levofloxacin removal in bioretention columns - Yidan Luo; Yuanwang Lan; Shuzhen Liang; Shuohan Yu; Mingshan Xue; Zuozhu Yin; Fang-Fang Shen; Xibao Li; Zhen Hong; Meiling Yan; Chan Xie; Bin Gao (Bioresource Technology, 2024)

Morphological and transcriptomic analyses of embryonic development of red-eared slider Trachemys scripta elegans - Jing Lin; Miaomiao Zhang; Fangbin Liang; Yunfang Ni; Jiani Zhang; Haitao Shi; Meiling Hong; Li Ding (Animal Reproduction Science, 2024)

Seasonal spermatogenesis in the red-eared slider (Trachemys scripta elegans): The roles of GnRH, actin cytoskeleton, and MAPK - Na Li; Wenzhuo Rao; Shiyu Dai; Muhammad Shahid Iqbal; Haitao Shi; Li Ding; Meiling Hong (Animal Reproduction Science, 2023)

Effect of ammonia stress on AMPK regulating-carbohydrate and lipid metabolism in Chinese striped-neck turtle (Mauremys sinensis) - Ijaz Khan; Yingnan Lu; Na Li; Haitao Shi; Li Ding; Meiling Hong; Zhenhua Fang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

The inhibition of miR-17-5p promotes cortical neuron neurite growth via STAT3/GAP-43 pathway - Liang Zhang; Zhijie Wang; Bo Li; Ziwei Xia; Xin Wang; Yucai Xiu; Zheng Zhang; Chuanjie Chen; Hong Song; Wenhua Li; Mei Yu; Meiling Zhang; et al. (Molecular Biology Reports, 2020)

Combination of NAD+ and NADPH Offers Greater Neuroprotection in Ischemic Stroke Models by Relieving Metabolic Stress - Qiao Huang; Meiling Sun; Mei Li; Dingmei Zhang; Feng Han; Jun Chao Wu; Kohji Fukunaga; Zhong Chen; Zheng-Hong Qin (Molecular Neurobiology, 2018)

Assessment of debris inputs from land into the river in the Three Gorges Reservoir Area, China - Jing Wan; Yonggui Wang; Meiling Cheng; Bernard A. Engel; Wanshun Zhang; Hong Peng (Environmental Science and Pollution Research, 2018)

Isolation and characterization of 20 microsatellite markers for the crab-eating frog Fejervarya cancrivora - Yitao Zheng; Lijun Wang; Meiling Hong; Meng Yao (Conservation Genetics Resources, 2016)

Endogenous level of TIGAR in brain is associated with vulnerability of neurons to ischemic injury - Lijuan Cao; Jieyu Chen; Mei Li; Yuan-Yuan Qin; Meiling Sun; Rui Sheng; Feng Han; Guanghui Wang; Zheng-Hong Qin (Neuroscience Bulletin, 2015)

Polymerase chain reaction analysis of laboratory generated bioaerosols - Zhai Junhui; Yang Ruifu; Che Fengxiang; Chen Meiling; Cui Hong (Aerobiologia, 1997)